1999
DOI: 10.1111/j.1600-0528.1999.tb02010.x
|View full text |Cite
|
Sign up to set email alerts
|

A 2‐year clinical study of two glass ionomer cements used in the atraumatic restorative treatment (ART) technique

Abstract: The purpose of the study was to evaluate, in a clinical study over 2 years, the deterioration of two glass ionomer cements used with the atraumatic restorative treatment (ART) technique or approach. Fifty-five Fuji IX and 45 ChemFil Superior restorations were placed randomly in 23 adult patients, mainly in small occlusal preparations in molar teeth. The restorations were placed in a dental hospital by one dentist using the ART technique. Photographs, radiographs and replicas were obtained at baseline and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 11 publications
3
7
1
Order By: Relevance
“…In this study, the sealants, regardless of their retention levels, showed to be beneficial. The caries-free teeth after 1 year were 98.5% for both tested groups and it is in accordance with other studies that presented rates of caries-free teeth varying from 96.1% to 100% after one year 3 , 8 10 , 13 , 14 , 17 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the sealants, regardless of their retention levels, showed to be beneficial. The caries-free teeth after 1 year were 98.5% for both tested groups and it is in accordance with other studies that presented rates of caries-free teeth varying from 96.1% to 100% after one year 3 , 8 10 , 13 , 14 , 17 .…”
Section: Discussionsupporting
confidence: 92%
“…In relation to the retention rates and the caries-incidence, there were no statistically significant differences between the experimental and test groups by gender, type of first molar and jaw at the 1 year recall. This result observed was comparable to those presented in literature 3 , 5 , 13 , 14 , 19 , probably due to standardization of procedures.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies have reported retention rates of high viscosity GIC sealants that vary considerably [30-33]. This variance may be explained by the clinical conditions (field setting) under which sealants are placed, the teeth selected for sealing, operator factors and inadequate training.…”
Section: Discussionmentioning
confidence: 99%
“…One way to overcome these shortcomings is to apply the replica method using die stone, which has been used successfully for evaluating restorations, 11,12 detecting developmental enamel defects 13 and measuring the cement thickness of placed crowns. 14 However, this method has rarely been used for assessing dental sealant retention.…”
Section: Introductionmentioning
confidence: 99%